The role of compaction in the diagenetic evolution of Pre-Salt Aptian deposits of Santos Basin, Brazil - Rodrigo B. Rossoni; Carla C. Porcher; Edinei Koester; Júlia S. Sobiesiak; Luis A.C. da Silva; André S. Mexias; Márcia E.B. Gomes; Camila W. Ramnani; Luiz F. De Ros (Sedimentary Geology, 2024)

A geoarchaeological review of Balzi Rossi, Italy: A crossroad of Palaeolithic populations in the northwest Mediterranean - D.D. Ryan; E. Starnini; M. Serradimigni; E. Rossoni-Notter; O. Notter; A. Zerboni; F. Negrino; S. Grimaldi; M. Vacchi; L. Ragaini; A. Rovere; A. Perego; et al. (Quaternary Science Reviews, 2024)

A model of distributed parameters for non-Fickian diffusion in grain drying based on the fractional calculus approach - Gustavo S. Matias; Fernando H. Lermen; Camila Matos; Douglas J. Nicolin; Clovis Fischer; Diogo F. Rossoni; Luis M.M. Jorge (Biosystems Engineering, 2023)

Tetrastischus howardi density and dispersal toward augmentation biological control of sugarcane borer - R H Barbosa; F F Pereira; A V A Motomiya; S O Kassab; C Rossoni; J B Torres; R M Mussury; P L Pastori (Neotropical Entomology, 2019)

Recovery of Arapaima sp. populations by community‐based management in floodplains of the Purus River, Amazon - T. A. Petersen; S. M Brum; F. Rossoni; G. F. V. Silveira; L. Castello (Journal of Fish Biology, 2016)
In the present study a unique dataset on population abundance in various community‐based management ( CBM ) and non‐ CBM areas is analysed to address the question of whether CBM can recover overexploited populations of Arapaima sp. in river‐floodplain ecosystems. All non‐ CBM areas possessed depleted Arapaima sp. populations with a mean density of 0·01 individuals ha −1 . Arapaima sp. population densities in all CBM areas changed over time from depleted to overexploited or well managed status, with a mean rate of increase of 77% year −1 . Rates of Arapaima sp. population recovery in CBM areas differed, probably reflecting differences in ecosystem productivity and compliance with management regulations. These results indicate that CBM schemes can be effective tools for the recovery and conservation of fish populations with non‐migratory life cycles in tropical river‐floodplain ecosystems.

Localization of stilbene synthase in Vitis vinifera L. during berry development - V. Fornara; E. Onelli; F. Sparvoli; M. Rossoni; R. Aina; G. Marino; S. Citterio (Protoplasma, 2008)